Accuracy of point‐of‐care crossmatching methods and crossmatch incompatibility in critically ill dogs - Marshall, Hayden (J Vet Intern Med, 2020)
BACKGROUND: The performance of commercial point‐of‐care crossmatch (CM) tests compared to laboratory tube agglutination CM is unknown. Additionally, there is limited information regarding CM incompatibility in ill dogs. OBJECTIVES: To determine if point‐of‐care major CM methods are accurate in detecting compatible and incompatible tests when compared to laboratory CM methods, and to identify factors associated with CM incompatibility in dogs. ANIMALS: Part 1 (prospective) included 63 client‐owned dogs potentially requiring blood transfusion. Part 2 (retrospective) included all dogs from part 1, plus medical records of 141 dogs with major CM results. METHODS: For part 1, major CM was performed using a tube agglutination assay (LAB‐CM), a gel‐based point‐of‐care test (GEL‐CM), and an immunochromatographic point‐of‐care test (IC‐CM). For part 2, medical record data were collected to determine rates of and risk factors for CM incompatibility. RESULTS: Kappa agreement between the LAB‐CM and GEL‐CM methods could not be calculated due to a relative lack of incompatible results. Kappa agreement between the LAB‐CM and IC‐CM methods was 0.16 (95% confidence interval [CI] = 0‐0.31, P = .007) indicating no agreement. The LAB‐CM incompatibility in transfusion‐naïve vs dogs that had a transfusion was 25% and 35%, (P = .3). CONCLUSIONS AND CLINICAL IMPORTANCE: Compared to laboratory methods, point‐of‐care methods evaluated in our study lacked sensitivity for detecting incompatibilities. Dogs had similar rates of major CM incompatibility regardless of transfusion history. This suggests CM testing prior to transfusion be considered in all dogs however our study did not investigate clinical relevancy of incompatible LAB‐CM.